External Load Evaluation in Elite Futsal: Influence of Match Results and Game Location with IMU Technology - Héctor Gadea-Uribarri; Carlos Lago-Fuentes; Ainhoa Bores-Arce; Víctor Emilio Villavicencio Álvarez; Sergio López-García; Santiago Calero-Morales; Elena Mainer-Pardos (Journal of Functional Morphology and Kinesiology)
The purpose of this study was to assess the external load demands in futsal, considering both home and away matches and their outcomes, in order to plan microcycles throughout the season based on the external load of each match. The external load of 10 players from a First Division team in the Spanish Futsal League was recorded throughout 15 official matches in the first half of the league championship. The players’ external load was monitored using OLIVER devices. To analyse the influence of the match outcome and location on the external load, a univariate general linear model (GLM) analysis was conducted with Bonferroni post hoc. There are no differences between the variables neither comparing results nor location factors, except for accelerations of 2 to 3 m/s2 (m) per minute and the number of accelerations of 2 to 3 m/s2 per minute, reporting higher value winnings at home than away (p < 0.05). The location and results are not factors that influence on external load in futsal matches, except the number and distance performed in accelerations and distance covered at a low to medium speed. These findings are important for planning microcycles and providing the appropriate dosage to each player to achieve optimal performance in matches.